Prostaglandin E(2) acts via bone marrow macrophages to block PTH-stimulated osteoblast differentiation in vitro - Choudhary, Shilpa (2013)
Intermittent PTH is the major anabolic therapy for osteoporosis while continuous PTH causes bone loss. PTH acts on the osteoblast (OB) lineage to regulate bone resorption and formation. PTH also induces cyclooxygenase-2 (COX-2), producing prostaglandin E(2) (PGE(2)) that can act on both OBs and osteoclasts (OCs). Because intermittent PTH is more anabolic in Cox-2 knockout (KO) than wild type (WT) mice, we hypothesized COX-2 might contribute to the effects of continuous PTH by suppressing PTH-stimulated differentiation of mesenchymal stem cells into OBs. We compared effects of continuous PTH on bone marrow stromal cells (BMSCs) and primary OBs (POBs) from Cox-2 KO mice, mice with deletion of PGE(2) receptors (Ptger4 and Ptger2 KO mice), and WT controls. PTH increased OB differentiation in BMSCs only in the absence of COX-2 expression or activity. In the absence of COX-2, PTH stimulated differentiation if added during the first week of culture. In Cox-2 KO BMSCs, PTH-stimulated differentiation was prevented by adding PGE(2) to cultures. Co-culture of POBs with M-CSF-expanded bone marrow macrophages (BMMs) showed that the inhibition of PTH-stimulated OB differentiation required not only COX-2 or PGE(2) but also BMMs. Sufficient PGE(2) to mediate the inhibitory effect was made by either WT POBs or WT BMMs. The inhibitory effect mediated by COX-2/PGE(2) was transferred by conditioned media from RANKL-treated BMMs and could be blocked by osteoprotegerin, which interferes with RANKL binding to its receptor on OC lineage cells. Deletion of Ptger4, but not Ptger2, in BMMs prevented the inhibition of PTH-stimulated OB differentiation. As expected, PGE(2) also stimulated OB differentiation, but when given in combination with PTH, the stimulatory effects of both were abrogated. These data suggest that PGE(2), acting via EP4R on BMMs committed to the OC lineage, stimulated secretion of a factor or factors that acted to suppress PTH-stimulated OB differentiation. This suppression of OB differentiation could contribute to the bone loss seen with continuous PTH in vivo.